Analisis sistem antrian model G/G/1 pada fasilitas layanan kesehatan - Aditya Rahadian Fachrur; Laura Novel Hutagaol; Rendiansyah Rendiansyah (Universitas Sultan Ageng Tirtayasa, 2022)
Health care is one of the services that must maintain excellent service quality, particularly in terms of patient wait times, including for XYZ health care facilities. XYZ health care services include administration or registration, health check-ups, and drug collection. Queues of patients are frequently encountered during the outpatient service process at XYZ health facilities. These queues often occur when patients perform registration administration, allegedly because there is only one registration counter. This problem will certainly affect patient satisfaction because service waiting time is a health facility customer satisfaction indicator. This study aims to analyze the queuing system for administrative services and health checks using the queuing theory method to obtain a queuing model and queuing performance. The results of this study indicate that the XYZ health facility queuing model is G/G/1/FIFO/I/I with an arrival rate for each service stage of 13 and 11 patients per hour, respectively, with 11 and 13 patients. Steady-state conditions are not met in administrative services because the arrival rate is higher than the service level, so the performance of the queuing system can be analyzed only on health check services, with the result that the probability of service facilities experiencing idle is 0.12. The average number of patients in the queue is one patient per hour, and the average number of patients in the system is four people per hour, while the waiting time for health check services is 37.0820 minutes per patient. The average length of time is 37.0820 minutes per patient. Patients are in the health care system for 41.9714 minutes per patient.